Novel Traveling Wave Solutions of Jaulent-Miodek Equations and Coupled Konno-Oono Systems and Their Dynamics - Avneesh Kumar; Krıpa Shankar Pandey; Raj Kumar; Anshu Kumar (Chaos Theory and Applications)
This research article deals with analytical solutions to two problems. The first is the (1+1)-coupled Jaulent-Miodek system of equations, which is associated with the energy-dependent Schrödinger potential, whereas the second problem, the system of coupled Konno-Oono equations relates to complexity and chaos in electromagnetic fields. Similarity reductions via Lie-symmetry analysis is performed for the systems to derive their analytical solutions. Since Lie symmetry involves arbitrary constants in the infinitesimals, this opens up more possibilities for getting a rich variety of analytical solutions for both real-life problems. The analytical solutions are supplemented graphically to understand them in a better way. Traveling wave profiles are obtained eventually. Solution for CKOEs are different from the earlier research (Kumar and Kumar 2022a; Kumar et al. 2022) as far as the authors are aware.